2009
DOI: 10.1075/lald.50.11gri
|View full text |Cite
|
Sign up to set email alerts
|

Temporal interface delay and root nonfinite verbs in Spanish-Speaking children with specific language impairment

Abstract: Existing research into speci c language impairment in Spanish utilizes primarily spontaneous production data and concludes that children do not have problems with verb niteness. In contrast, we show, through a new receptive measure, the "Grammaticality Choice Task", that the distribution of the 2 most common errors in child Spanish is su cient to distinguish language-impaired children from age and language control groups. We conclude that niteness marking on verbs is a promising clinical marker for SLI in Span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…Here, we found that children with BLI produced more OCP omissions in the postverbal (non-finite) than the preverbal (finite) elicitation context. Despite other studies linking nonfiniteness errors with BLI (Bedore & Leonard, 2001;Grinstead et al, 2009), these results do not implicate finiteness as a potential source of difficulty in school-aged children. Additionally, cross-linguistic influence which would favor the English postverbal placement was not evident.…”
Section: Object Clitic Pronounscontrasting
confidence: 99%
See 1 more Smart Citation
“…Here, we found that children with BLI produced more OCP omissions in the postverbal (non-finite) than the preverbal (finite) elicitation context. Despite other studies linking nonfiniteness errors with BLI (Bedore & Leonard, 2001;Grinstead et al, 2009), these results do not implicate finiteness as a potential source of difficulty in school-aged children. Additionally, cross-linguistic influence which would favor the English postverbal placement was not evident.…”
Section: Object Clitic Pronounscontrasting
confidence: 99%
“…In Spanish, the substitution of a third person singular inflection for a third person plural inflection is considered to be a non-finite error, comparable to the English bare stem phenomenon (Bosch & Serra, 1997). It is argued that data from spontaneous samples may be less reliable for uncovering potential areas of deficit, seeing as the subjectverb agreement in null subject languages does not always prove obligatory, thereby resulting in the possibility that errors regarding the substitution of third person singular verbs for third person plural forms may go undetected in situations where the subject has not been realized (Grinstead, De la Mora, Pratt & Flores, 2009). In light of this complication, Grinstead et al (2009) administered a grammaticality judgment task to Spanish speakers with TD and LI which revealed a higher acceptance of nonfinite constructions by children with LI.…”
Section: Verb Inflectionsmentioning
confidence: 99%
“…Grinstead, De la Mora, Pratt & Flores (2009) show that in a sample of 27 monolingual Spanish-speaking children, 9 of whom are diagnosed with SLI (mean age = 5;6; MLU w = 3.0) , 9 of whom are age matches (mean age = 5;6) and 9 of whom are MLU w matches (MLU w = 3.0), the children with SLI were significantly worse than either the age matches (p < .001) or the MLU matches (p < .001) at recognizing whether a finite utterance with an overt subject (e.g. Pratt & Flores (2009, p. 256) Similarly, Grinstead, De la Mora, Vega-Mendoza & Flores (2009) show, using an elicited production test, that 19 monolingual Spanish-speaking children with SLI (mean age = 67 months) perform significantly more poorly than do an age-matched control group of 19 typically-developing children at producing finite verb forms, t(36) = 3.392, p = .002, illustrated in Summarizing, though much has been learned about developmental syntax through the study of spontaneous production data, it cannot be the only tool used to determine what children know.…”
Section: Root Infinitives In Null Subject Languages: Methodological Cmentioning
confidence: 99%
“…in which a third singular present verb form occurs with a first person singular pronoun (cf. Pratt & Grinstead 2007Grinstead, De la Mora, Pratt & Flores 2009). These plausibly bare stem forms do not form part of any compound finite utterance.…”
mentioning
confidence: 99%
See 1 more Smart Citation